(untitled) (Práxis Educativa, 2017)
Children and young people are the main actors in the classroom. Despite this reality, the experiences of the minors in the past are absent in the history of what children and young Chileans learn. In the following paper, we show the results obtained from the analysis of the Chilean curriculum of the role of children and young people’s inclusion/exclusion in school history. At the same time, we compare the results obtained from the analysis of curriculum to the ideas and representations of Chilean students about their own role and their peers in history. The research had a marked qualitative and interpretative character, as we worked on interpreting the statements present on the purposes of the ministerial agenda in relation to History, Geography and Social sciences, as well as on the speeches of the students regarding the role of children and young people in history. Keywords: Agenda. Protagonists of history. Representations of students.